Shipborne rotating shadowband radiometer data of spectral irradiance components and aerosol optical depth during Polarstern cruises PS83, PS95, PS98, PS102 and PS113 - Jonas Witthuhn; Hartwig Deneke; Andreas Macke (PANGAEA, 2020)
The dataset consists of continuous measurements of global, direct and diffuse spectral irradiance and aerosol optical thickness during Polarstern cruises PS83, PS95, PS98, PS102 and PS113 with the GUVis-3511 radiometer and the BioSHADE accessory build by Biospherical Instruments Inc.. To derive this dataset, the raw GUVis-3511 data is processed as described in Witthuhn et al. 2017, doi:10.5194/amt-10-709-2017 A first version of this data from cruise PS83 is already published at pangaea: doi:10.1594/PANGAEA.872377 Since then the processing algorithm receives major updates as described in Witthuhn et al. 2019 ( in review, doi:10.5194/amt-2019-321).